(3Whb GdUGOM GdeaUd HLhGgQ GdHjGf GdhGVMs - (3GdchcHGfj , jhSa Hf Ydj Hf GdgGOj GdchcHGfj GdUfYGfj,J (B1116 (3g` s
(3ChdgG (B:s
(3CMeO ef Whbfi HGdEfYGe , aSLYJ HMeOg Ydi bUH GdCbdGe hHYO Pdc JHOC GdJQGLe HGdTQja GdQVi s
(3BNQgG (B:s
(3BNQg eHJhQ jfJgi CKfGA JQLeI jMji Hf EHQGgje Hf Ydi Hf LMGa GdMHhQi hBNQ GdehLhO efg (B:" (3hGHf HgQGf Mci Yf HYV GdeJJbOejf EHGMI GdZfGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdcJGH ai LRFjf NUU GdChd GdJQGLe GdeJbOejfs
(3hGdKGfi ddYUQjjfs
(3hai Chd GdcJGH JbGQjX heOGFM deDdags
(3hbUjOg ai eOM GdQShd Udi Gddg Ydjg hSde s
(3GfXQ SLY GdeWhb GdcJGH GdChd ai GdeLehYI s
(3ai JQGLe GdCOHGA GdeJbOejf hGdeYGUQjf ddeDda s
Keywords: (3GdJGQjNs